Effect of Listing Age, Liquidity, Company Size and Leverage on Information Asymmetry - Mohamad Zulman Hakim; Kharinda Mitha Defitri; Saleman Hardi Yahawi; Hamdani; Imam Hidayat; Indra Gunawan Siregar (International Journal of Economics, Business and Innovation Research, 2022)
The study aims to empirically prove the effect of listing age, firm size, liquidity and leverage on information asymmetry. The population in this study uses the non – cyclical consumer sector. The sampling technique used purposive sampling. Methods of data analysis using Panel Data Regression Analysis. These results indicate that listing age has no effect on information asymmetry, liquidity has no effect on information asymmetry, company size has no negative effect on information asymmetry and leverage has no effect on information asymmetry.